The Moderating Effect of Physical Activity on the Association Between Cognition and Depression Among Middle-Aged and Older Adults: A Differential Analysis by European Regions - De Moraes-Ferrari, G (SAGE Publications Inc., 2025)
This study aimed to investigate the moderating effect of moderate-to-vigorous physical activity (MVPA) on the association between cognition and depression in individuals aged 50 years or older living in 27 European countries and to explore differences between four European regions (West, North, South, East). Categorical moderation analysis was performed with 41,878 individuals using data from the SHARE database. The variables analyzed were depression (EURO-D scale), Cognition Index (CogId), and self-reported MVPA. Western and Northern European regions indicated higher CogId and MVPA scores and lower depression than those in the South and East. MVPA frequency proved to be a significant moderator on the association between cognition and depression, with notable differences between regions. Especially in Southern and Eastern Europe, it would be important to create strategies that promote MVPA, which is fundamental to the mental and cognitive health of middle-aged and older adult populations. © The Author(s) 2025